The Effect of Acceptance and Commitment Group Therapy on Emotional Maturity in Female Adolescents With Visual Impairment - Fatemeh Mirmohammadi; Masoume Pourmohamadreza-Tajrishi (University of Social Welfare and Rehabilitation Sciences, 2024)
Objective Adolescents with visual impairments have less opportunity to adapt emotionally to the environment and, as a result, experience more social and academic problems. One of the most critical needs of adolescence is maintaining emotional balance while confronting the stressful factors of puberty and environmental expectations. As visual impairment adversely influences adolescents' emotional maturity, helping teenagers adapt to challenging conditions is one of the main goals of a social and educational system. The purpose of the present study was to determine the effect of acceptance and commitment therapy (ACT) on the emotional maturity of female adolescents with visual impairment. Materials & Methods The current quasi-experimental study employed a pre-test and post-test and a follow-up design with a control group. A total of 82 females aged 14 to 18 from an educational community special for visually impaired individuals were assessed using the emotional maturity scale (EMS) in the academic year 2020-2021. Among the 33 volunteers who scored 180 and above in the EMS, 28 individuals were selected according to the inclusion criteria and matched based on their age and educational level via convenience sampling. All participants were randomly assigned to the experimental and control groups (14 individuals each). The experimental group attended 10 therapeutic sessions and received acceptance and commitment group therapy for two months (twice a week, 60 minutes per session). However, the control group only participated in the educational community's make-up empowering programs (including lessons curriculum plans and music training). All participants completed the EMS after the last intervention session and then 8 weeks later as a follow-up. The data were analyzed using the Shapiro-Wilk test, Levene test, M. Box test, multivariate analysis of covariance, and dependent t-test by SPSS software, version 22. Results The results of the Shapiro-Wilk test, Levene test, and M. Box test confirmed the normality of the distribution of scores, the homogeneity of variances, and the homogeneity of line slope, respectively. The results of multivariate analysis of covariance indicated that attendance of the experimental group in the acceptance and commitment group therapy sessions has led to a significant increase (P<0.05) in emotional maturity scores and its components: emotional stability, emotional progression, social adjustment, personality integration, and independence. Also, the ACT program changed the experimental group's emotional maturity and components as follows: 90%, 69%, 59%, 55%, 92%, and 68% for emotional stability, emotional progression, social adjustment, personality integration, and independence, respectively. In addition, the results of the dependent t-test to compare the emotional maturity of the experimental group in post-test and follow-up stages indicated that the effect of the group therapy has remained on emotional maturity and its areas even 8 weeks later (P<0.05). In addition, the results of the dependent t-test showed a significant difference between the emotional maturity of the experimental group in the post-test and follow-up stages. It means that the effect of group therapy has remained on emotional maturity and its components even 8 weeks later. Conclusion Since the acceptance and commitment group therapy has improved the emotional maturity and its components in adolescents with visual impairment, it seems that the ACT is important as a proper and complementary method in empowerment programs for adolescents. The ACT helps adolescents recognize, accept, and control negative feelings or thoughts by increasing their emotional maturity. Therefore, the ACT is a proper method for hindering the problems relating to emotional maturity and probably prevents the occurrence of future problems in adulthood.